Sensitivity to Vocalization Pitch in the Caudal Auditory Cortex of the Marmoset: Comparison of Core and Belt Areas - Zhu, Shuyu; Allitt, Benjamin; Samuel, Anil; Lui, Leo; Rosa, Marcello G. P.; Rajan, Ramesh (Frontiers in Systems Neuroscience, 2019)
Based on anatomical connectivity and basic response characteristics, primate auditory cortex is divided into a central core surrounded by belt and parabelt regions. The encoding of pitch, a prototypical element of sound identity, has been studied in A1 but little is known about how it is encoded and represented beyond A1. The caudal auditory belt and parabelt cortical fields process spatial information but also contain information on non-spatial aspects of sounds. In this study, we examined neuronal responses in these areas to pitch-varied marmoset vocalizations, to derive the consequent representation of pitch in these regions and the potential underlying mechanisms, to compare to the encoding and representation of pitch of the same sounds in A1. With respect to response patterns to the vocalizations, neurons in caudal medial belt (CM) showed similar short-latency and short-duration response patterns to A1, but caudal lateral belt (CL) neurons at the same hierarchical level and caudal parabelt (CPB) neurons at a higher hierarchical level showed delayed or much delayed response onset and prolonged response durations. With respect to encoding of pitch, neurons in all cortical fields showed sensitivity to variations in the vocalization pitch either through modulation of spike count or of first spike latency. The utility of the encoding mechanism differed between fields: pitch sensitivity was reliably represented by spike count variations in A1 and CM, while first spike latency variation was better for encoding pitch in CM and CPB. In summary, our data show that (a) the traditionally-defined belt area CM is functionally very similar to A1 with respect to the representation and encoding of complex naturalistic sounds, (b) the CL belt area at the same hierarchical level as CM and the CPB parabelt area at a higher hierarchical level have very different response patterns and appear to use different pitch-encoding mechanisms, and (c) caudal auditory fields, proposed to be specialized for encoding spatial location, can also contain robust representations of sound identity.